Mathematical Literacy Performance of Junior High School Students in Solving PISA Problems - Mufidah, Siti; Sudirman; Muksar, Makbul (Journal of Education Reseach and Evaluation, 2025)
Mathematical literacy has been widely studied by mathematics education experts. Mathematical literacy is an individual’s competence to apply mathematics to solve real-world problems and make appropriate decisions. This study aims to explore the mathematical literacy performance of junior high school students in solving PISA problems. The research method used was qualitative, with eight students as research subjects, each with different levels of mathematical literacy. Data analysis was conducted using the framework proposed by Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The research framework was based on the eight levels of PISA mathematical literacy and Polya's problem-solving stages. The study results showed that students' abilities in understanding the problem, devising a plan, carrying out the plan, and looking back differed based on their level of mathematical literacy. Students at levels 1c, 1b, and 1a demostrated  problem-solving abilities limited to basic memory capacity. Students at levels 2, 3, and 4 could only solve problems involving procedural skills. Meanwhile, students at levels 5 and 6 could solve problems with in-depth analytical reasoning and follow-up reflection. These findings have implications for teachers to design context-based learning that supports the development of students' mathematical literacy.